Energy, exergy and economic (3E) evaluations of a novel power generation system combining supercritical water gasification of coal with chemical heat recovery. (15th January 2023) - Chen, Zhewen; Zhou, Qi; Zhang, Yuming; Zhang, Xiaosong
Highlights: A novel power system with integrated SCWG of coal and chemical heat recovery is proposed, and analyzed. Energy, exergy and economic analyses are conducted out. Maximum power generation efficiency of 49.06% is obtained. The levelized cost of electricity of the novel power system is 0.2963 ¥/kWh. Abstract: Supercritical water gasification (SCWG) is a promising clean coal utilization technology. A proposed power system with integrated coal SCWG, supercritical turbine, gas turbine and chemical heat recovery is proposed in this paper. And the power system with integrated combined cycle and parallel heat recovery is re-proposed for structure simplification and efficiency enhancement. With a gasification condition of 660℃/250 bar, and a coal-water-slurry concentration of 11.3 %, the efficiencies of the proposed system and the system with parallel heat recovery are 49.06 % and 47.93 %, respectively. The power efficiency of the proposed system is greatly improved compared with the traditional systems. This is mainly due to the reasonable use of the pressure energy of the gasification product through the supercritical turbine, the release and use of high level chemical energy stored in the syngas in the gas turbine, and chemical heat recovery of the sensible heat of the flue gas from the gas turbine. Exergy and economic analyses are also performed. The levelized cost of electricity (LCOE) of the proposed power system is 0.2963 ¥/kWh. The power system proposed herein can be considered as one of the suitable options to achieve the carbon peak and carbon neutrality goals.